A long period grating based directional flow sensor - Buggy, Stephen J.; James, Stephen W.; Tatam, Ralph P. (International Society for Optical Engineering; 1999, 2008)
A chirped long period grating (LPG) is used as a directional flow sensor by monitoring the change in the transmission spectrum upon immersion in an oil of refractive index higher than that of the fibre cladding. The change in profile of an attenuation band is shown to depend on the direction of immersion, indicating the possibility of using such devices in applications such as resin flow sensing in the manufacture of fibre reinforced plastic composite structures.